A point‐based tool to predict conversion from mild cognitive impairment to probable Alzheimer's disease. Issue 6 (3rd February 2014) - Barnes, Deborah E.; Cenzer, Irena S.; Yaffe, Kristine; Ritchie, Christine S.; Lee, Sei J.; ,
Abstract: Background: Our objective in this study was to develop a point‐based tool to predict conversion from amnestic mild cognitive impairment (MCI) to probable Alzheimer's disease (AD). Methods: Subjects were participants in the first part of the Alzheimer's Disease Neuroimaging Initiative. Cox proportional hazards models were used to identify factors associated with development of AD, and a point score was created from predictors in the final model. Results: The final point score could range from 0 to 9 (mean 4.8) and included: the Functional Assessment Questionnaire (2‒3 points); magnetic resonance imaging (MRI) middle temporal cortical thinning (1 point); MRI hippocampal subcortical volume (1 point); Alzheimer's Disease Cognitive Scale—cognitive subscale (2‒3 points); and the Clock Test (1 point). Prognostic accuracy was good (Harrell's c = 0.78; 95% CI 0.75, 0.81); 3‐year conversion rates were 6% (0‒3 points), 53% (4‒6 points), and 91% (7‒9 points). Conclusions: A point‐based risk score combining functional dependence, cerebral MRI measures, and neuropsychological test scores provided good accuracy for prediction of conversion from amnestic MCI to AD.